URGENSI BELAJAR MENURUT AL-QUR’AN KAJIAN SURAT AL-ALAQ AYAT 1-5 : Studi Tafsir Ibnu Katsir dan Tafsir Al-Misbah - Sunani, Eneng (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
Seeing the fact that the Qur'an is the Word of Allah SWT. which was revealed to the Prophet Muhammad SAW. as a guide for humans in arranging their lives, in order to obtain inner and outer happiness, the world and the hereafter. The concepts brought by the Qur'an are always relevant to the problems faced by man, because he came down to dialogue with every people he encountered, as well as offer solutions to the problems he faced, whenever and wherever they were. The purpose of this study is to find out the urgency of learning according to the Qur'an, the study of Surah Al-Alaq verses 1-5. Data from this study was obtained through data collection, so in the analysis the author used a literature review, then the study began with the implementation of the literature. From the results of the data processing, it is concluded that the content of Surah Al-Alq verses 1-5 is: 1). According to Tafsir Ibn Kastir is that we are commanded to always conduct an investigation into everything that we do not know, so that we master, evidence of the mercy of Allah SWT. It is that he has taught man through the intercession of the Qur'an, 2). According to Tafsir Al-Misbah is Islam commands that we learn to read and write and study science in order to increase our degree as creatures of Allah the most glorious, we are encouraged to be able to breed the knowledge that Allah has bestowed on us